2005
DOI: 10.1051/0004-6361:20053272
|View full text |Cite
|
Sign up to set email alerts
|

On the formation and evolution of magnetic chemically peculiar stars in the solar neighborhood

Abstract: In order to put strict observational constraints on the evolutionary status of the magnetic chemically peculiar stars (CP2) of the upper main sequence, we have investigated a well established sample of galactic field CP2 objects within a radius of 200 pc from the Sun in the (X, Y) plane. In total, 182 stars with accurate parallax measurements from the Hipparcos satellite were divided into Si, SiCr and SrCrEu subgroups based on classification resolution data from the literature. Primarily, it was investigated i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
3
18
2
Order By: Relevance
“…Note that, in contrast to the results of Pöhnl et al (2005) and Kochukhov & Bagnulo (2006), both of whom found a deficiency of young Ap stars with masses below 2 M , all three of the lowmass stars in our survey are fairly close to the ZAMS; the largest fractional age among these stars is 0.16. This effect probably results from the fact that the main sequence lifetime of such stars (10 9 yr or more) is considerably longer than the ages of most clusters in our sample.…”
Section: Does Magnetic Fields Strength Change With With Time?contrasting
confidence: 99%
See 3 more Smart Citations
“…Note that, in contrast to the results of Pöhnl et al (2005) and Kochukhov & Bagnulo (2006), both of whom found a deficiency of young Ap stars with masses below 2 M , all three of the lowmass stars in our survey are fairly close to the ZAMS; the largest fractional age among these stars is 0.16. This effect probably results from the fact that the main sequence lifetime of such stars (10 9 yr or more) is considerably longer than the ages of most clusters in our sample.…”
Section: Does Magnetic Fields Strength Change With With Time?contrasting
confidence: 99%
“…This result, together with the results of Bagnulo et al (2003), Pöhnl et al (2005), Kochukhov & Bagnulo (2006), and our own survey, lead us to reject the hypothesis that stars with M ≤ 3 M becomes magnetic only after they have spent a significant fraction of their life in the main sequence.…”
Section: Does Magnetic Fields Strength Change With With Time?mentioning
confidence: 60%
See 2 more Smart Citations
“…Knowledge of the evolution of the magnetic field and its geometry, especially of the distribution of the obliquity angle β (orientation of the magnetic axis with respect to the rotation axis) is essential to understand the physical processes taking place in these stars and the origin of their magnetic fields (fossil versus contemporary dynamo). Early studies of the evolution of some characteristics of magnetic Corresponding author: shubrig@eso.org Ap and Bp stars were based on smaller stellar samples (e.g., North 1985;Hubrig, North & Mathys 2000;Hubrig, North & Szeifert 2005), or on stellar samples which included CP stars with not well-defined magnetic field strengths or rotation periods (e.g., Rüdiger & Scholz 1988;Pöhnl, Paunzen & Maitzen 2005;Kochukhov & Bagnulo 2006). …”
Section: Introductionmentioning
confidence: 99%